Activated Clotting Time to Guide Heparin Dosing in Non–ST-Segment–Elevation Acute Coronary Syndrome Patients Undergoing Percutaneous Coronary Intervention and Treated With IIb/IIIa Inhibitors: Impact on Ischemic and Bleeding Outcomes. (June 2018) - Dillinger, Jean-Guillaume; Ducrocq, Gregory; Elbez, Yedid; Cohen, Marc; Bode, Christoph; Pollack, Charles; Nicolau, José C.; Henry, Patrick; Kedev, Sasko; Wiviott, Stephen D.; Sabatine, Marc S.; Mehta, Shamir R.; et al.
Abstract : Background—: Monitoring anticoagulation with activated clotting time (ACT) has been proposed to reduce ischemic or bleeding events. However, the value of using ACT to improve outcomes is uncertain. This study sought to determine the relationship between ACT and outcomes during percutaneous coronary intervention in patients with non–ST-segment–elevation acute coronary syndrome (NSTE-ACS) treated by unfractionated heparin with GPIs (glycoprotein IIb/IIIa inhibitors). Methods and Results—: From the randomized TAO trial (Treatment of Acute Coronary Syndromes With Otamixaban), we analyzed the value of ACT to predict ischemic and bleeding outcomes in the 3275 patients receiving unfractionated heparin plus eptifibatide. Ischemic and safety outcomes were analyzed according to ACT to determine the best threshold. Median peak ACT was 225 s. There was no correlation ( r =−0.02; P =0.24) between the unfractionated heparin dose received and the ACT value before percutaneous coronary intervention. There was no evidence of a nonlinear association between ACT and either ischemic or bleeding events ( P =0.66; P =0.07). No threshold was found to predict ischemic complications. Conversely, increased bleeding was observed with ACT >230 s with an optimal threshold of ACTs ≥250 s (4.53% versus 6.17%; odds ratio, 1.46; 95% confidence interval, 1.04–2.06; P =0.028). This optimal threshold varied according to access site: ≥250 s (6.86% versus 10.18%; odds ratio, 1.57; 95% confidence interval, 1.00–2.45; P =0.047) by femoral approach and ≥290 s (2.86% versus 5.43%; odds ratio, 2.24; 95% confidence interval, 1.05–4.44; P =0.027) by radial approach. Conclusions—: In the TAO trial, peak procedural ACT ≥250 s was associated with increased bleeding risk in non–ST-segment–elevation acute coronary syndrome patients treated with unfractionated heparin plus GPIs. This threshold was increased to 290 s when performing radial approach. Clinical Trial Registration—: URL:https://www.clinicaltrials.gov . Unique identifier: NCT01076764. Abstract : Supplemental Digital Content is available in the text.